Cosmic Four-Fermion Neutrino Secret Interactions, Enhancement, and Total Cross Section - Gamboa-Rios, J; Mendez-Ferrada, F (American Physical Society, 2015)
The scattering of neutrinos assuming a "secret" interaction at low energy is considered. To leading order in energy, the two-body potential is a δ-potential, and it is used as a motivation to study generic short-range elastic interactions between neutrinos. The scattering cross section and Sommerfeld enhancement depend on two phenomenological parameters deriving from the exact form of the potential, akin to "renormalized" coupling constants. Repulsive potentials lead to a decrease in the total cross section, resulting in an enhancement of the neutrino density. For attractive potentials of the right form, substantial Sommerfeld enhancement can appear. © 2015 American Physical Society.